T cells as key players for bone destruction in gouty arthritis? - Harre, Ulrike; Derer, Anja; Schorn, Christine; Schett, Georg; Herrmann, Martin (Arthritis Research & Therapy, 2011)
The deposition of monosodium urate (MSU) crystals in synovial fluid and tissue leads to gouty arthritis frequently associated with synovial inflammation and bone erosions. The cellular mechanism that links MSU crystals to an increased number of osteoclasts has not yet been fully understood. In a recent issue of Arthritis Research & Therapy Lee and colleagues proposed that bone destruction in chronic gouty arthritis is at least in part dependent on expression by T cells of receptor activator of NF-κB ligand (RANKL). The authors showed that pro-resorptive cytokines such as IL-1β, IL-6, and TNFα are expressed within tophi and stromal infiltrates. In vitro stimulation with MSU crystals revealed monocytes as a source for these cytokines, whereas T cells produce RANKL, the major trigger of osteoclastogenesis. © 2011 BioMed Central Ltd.
Created from Fastlane, Scopus look-up